Continuous Positive Airway Pressure Mitigates Opioid-induced Worsening of Sleep-disordered Breathing Early after Bariatric Surgery. (July 2016) - Zaremba, Sebastian; Shin, Christina H.; Hutter, Matthew M.; Malviya, Sanjana A.; Grabitz, Stephanie D.; MacDonald, Teresa; Diaz-Gil, Daniel; Ramachandran, Satya Krishna; Hess, Dean; Malhotra, Atul; Eikermann, Matthias
Abstract : Background: Bariatric surgery patients are vulnerable to sleep-disordered breathing (SDB) early after recovery from surgery and anesthesia. The authors hypothesized that continuous positive airway pressure (CPAP) improves postoperative oxygenation and SDB and mitigates opioid-induced respiratory depression. Methods: In a randomized crossover trial, patients after bariatric surgery received 30% oxygen in the postanesthesia care unit (PACU) under two conditions: atmospheric pressure and CPAP (8 to 10 cm H2 O). During 1 h of each treatment, breathing across cortical arousal states was analyzed using polysomnography and spirometry. Arousal state and respiratory events were scored in accordance with American Academy of Sleep Medicine guidelines. Data on opioid boluses in the PACU were collected. The primary and secondary outcomes were the apnea hypopnea index (AHI) and apnea after self-administration of opioids in the PACU. Linear mixed model analysis was used to compare physiologic measures of breathing. Results: Sixty-four percent of the 33 patients with complete postoperative polysomnography data demonstrated SDB (AHI greater than 5/h) early after recovery from anesthesia. CPAP treatment decreased AHI (8 ± 2/h vs. 25 ± 5/h, P < 0.001), decreased oxygen desaturations (5 ± 10/h vs . 16 ± 20/h, P < 0.001), and increased the mean oxygen saturation by 3% ( P = 0.003). CPAP significantly decreased the respiratory-depressant effects observed during wakefulness–sleep transitions without affecting hemodynamics. The interaction effects between CPAP treatment and opioid dose for the dependent variables AHI ( P < 0.001), inspiratory flow ( P = 0.002), and minute ventilation ( P = 0.015) were significant. Conclusions: This pharmacophysiologic interaction trial shows that supervised CPAP treatment early after surgery improves SDB and ameliorates the respiratory-depressant effects of opioids without undue hemodynamic effects. Abstract : This prospective, randomized, cross over trial compared the apnea hypopnea index (AHI) with and without continuous positive airway pressure (CPAP) in 38 morbidly-obese patients and found that the CPAP reduced the AHI by 69% and was more effective during non-rapid eye movement sleep than during wakefulness. The AHI was worsened by self-administered opioid for pain and the CPAP application effectively mitigated the AHI deterioration.